Health implications of established and emerging stressors: design of the prospective New Jersey Population Health Cohort (NJHealth) Study - Dawne M Mouzon; Paul Duberstein; Joel C Cantor; William T Hu; Stephanie M Bergren; Mara Getz Sheftel; Steven B Cohen; Katherine B Morton; Dinesh Mendhe; Margaret Koller (BMJ Open)
Introduction Some stressors, like the death of a partner, are common and rigorously studied, while others, such as those related to climate change or social media, are just emerging and in need of systematic research. The New Jersey Population Health Cohort (NJHealth) Study aims to characterise established and emerging stressors and delineate the pathways through which they influence health, especially among groups likely to experience chronic exposure to stressors including immigrants, people of colour, multigenerational families and low-income families.Methods and analysis A prospective cohort, the NJHealth Study is recruiting 8000 NJ residents aged 14 and older using probabilistic and purposive methods to include members of multigenerational families, marginalised racial/ethnic and low-income populations, and recent immigrant groups. Building on ecosocial, life course and stress process models, the NJHealth Study employs multimodal data collection to comprehensively measure stress-related factors at individual and societal levels. Interviews include self-assessments of individual and societal stressors, potential stress buffers and amplifiers, and health and well-being outcomes, including cognitive function, activity limitations and self-reported health. In addition, salivary DNA, fasting plasma, health assessments and actigraphy data are collected from selected participants; and existing electronic health records, health insurance claims, social service and employment data, and vital records are linked. NJ’s socioeconomic and demographic diversity make it an exceptional setting for the study. Strong community and stakeholder engagement supports effective translation of research findings into practical policy and programme applications.Ethics and dissemination The study was approved by the WCGIRB (Study #1321099) (formerly Western IRB). Informed consent is obtained from participants for each source of participant-level data as well as linked administrative and clinical records. Findings will be reported to study participants, funding bodies, governmental and policy stakeholders, presented at scientific meetings and submitted for peer-review publication.